Risk Factors for Mortality of Pediatric Patients Without Underlying Diseases - Ling-Sai Chang; Ho-Chang Kuo; Chieh-Chiang Wu; Hong-Ren Yu; Lin Wang; Hsueh-Wen Chang; Kuender D. Yang (Pediatrics and Neonatology)
In this study, we investigated the risk factors for in-hospital mortality of children beyond infancy with and without underlying diseases. Methods: We performed a retrospective review of all deceased patients aged 1–18 years at Chang-Gung Memorial Hospital-Kaohsiung from 2000 to 2009. The patients were divided into two groups; those with and without underlying diseases. Demographic data, clinical characteristics, and initial laboratory data were analyzed to correlate the risk factors for mortality of pediatric patients with and without underlying diseases. Results: A total of 131 deceased children were found from 2000 to 2009. Forty children were previously healthy (without underlying diseases), whereas 91 had previous underlying diseases. Children with cardiovascular or central nervous system (CNS) infections had a significantly greater risk of mortality than did those without underlying diseases (p=0.004 and p=0.0004, respectively). More cardiovascular and fewer hematologic abnormalities at admission were found in patients without underlying diseases. In multiple logistic regression, it was found that cardiovascular (p=0.006) or CNS infections (p=0.012), consciousness change at admission (p=0.013), and higher liver enzyme levels were most significantly associated with deceased children without underlying diseases. Conclusion: Results from this study suggest that mortality in pediatric patients without underlying diseases is most frequently found in younger children with CNS and cardiovascular infections, consciousness change, and high liver enzyme levels at admission. Results from this analysis will provide information for the awareness of fatal outcomes in previously healthy children.